Impact of Mitochondrial Ca2+-Sensitive Potassium (mBKCa) Channels in Sildenafil-Induced Cardioprotection in Rats. - Friederike Behmenburg; Marianne Dorsch; Ragnar Huhn; David Mally; André Heinen; Markus W Hollmann; Marc M Berger (PLoS ONE, 2015)
Background Mitochondrial large-conductance Ca2+-sensitive potassium (mBKCa) channels are involved in myocardial ischemic preconditioning. Their role in sildenafil-induced cardioprotection is unknown. We investigated whether sildenafil-induced acute cardioprotection is mediated by activation of mBKCa channels in the rat heart in vitro. Methods Male Wistar rats (n = 8 per group) were randomized and anesthetized with pentobarbital (90 mg/kg). Hearts were isolated, mounted on a Langendorff system and perfused with Krebs-Henseleit buffer at a constant pressure of 80 mmHg. Hearts underwent 30 min of global ischemia followed by 60 min of reperfusion. At the end of the experiments infarct size was determined by TTC staining. In the control group rats were not further treated. Sildenafil (3 μM) was administered over 10 min before the beginning of ischemia. The mBKCa channel inhibitor paxilline (1 μM) was administered with and without sildenafil before the onset of ischemia. The pathway underlying sildenafil-induced cardioprotection was further investigated with the protein kinase G blocker KT5823 (1 μM). Myocardial cGMP concentration was measured by ELISA. Data (mean±SD) were analysed with a one and two-way analysis of variance as appropriate. Results In control animals infarct size was 52±8%. Sildenafil increased cGMP concentration and reduced infarct size to 35±6% (P<0.05 vs. control). Paxilline and KT5823 completely blocked sildenafil-induced cardioprotection (paxilline+sildenafil: 50±8%, KT5823+sildenafil: 45±8%; both P<0.05 vs. sildenafil). Functional heart parameters and coronary flow were not different between the study groups. Conclusion This study shows that in male rats protein kinase G-dependent opening of mBKCa channels plays a pivotal role in sildenafil-induced cardioprotection.